2011
DOI: 10.1080/02786826.2011.558136
|View full text |Cite
|
Sign up to set email alerts
|

An Asymptotic Analysis of Differential Electrical Mobility Classifiers

Abstract: An asymptotic analysis of balanced flow operations of differential mobility analyzers (DMAs) and a new class of instruments that includes opposed migration aerosol classifiers (OMACs) and inclined grid mobility analyzers (IGMAs) provides new insights into the similarities and differences between the devices. The characteristic scalings of different instruments found from minimal models are shown to relate the resolving powers, dynamic ranges, and efficiencies of most such devices. The resolving powers of all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Equations 27 and 28, respectively). In the diffusion-limited regime, assuming that the transfer function of the MMO-DMA is Gaussian, we derive the diffusion-limited resolution R diff i for each outlet (Equations (97), (99), and (100)), using the approach followed by Flagan (1999) and Downard et al (2011). Combining the two limiting cases (i.e., for nondiffusing and for diffusing particles), we further derive an approximate resolution R approx i (Equations (107) and (108)) for balanced flows only, which can be applied over the entire range of particle mobilities and diffusional broadening parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations 27 and 28, respectively). In the diffusion-limited regime, assuming that the transfer function of the MMO-DMA is Gaussian, we derive the diffusion-limited resolution R diff i for each outlet (Equations (97), (99), and (100)), using the approach followed by Flagan (1999) and Downard et al (2011). Combining the two limiting cases (i.e., for nondiffusing and for diffusing particles), we further derive an approximate resolution R approx i (Equations (107) and (108)) for balanced flows only, which can be applied over the entire range of particle mobilities and diffusional broadening parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Flagan (1999) showed that for small particles, the resolution is proportional to the square root of the applied voltage. Downard et al (2011) extended this approach for the opposed migration aerosol classifiers (OMACs) and the inclined grid mobility analyzers (IGMAs), and showed that at low voltages both these instruments exhibit better resolution compared with that of the DMA. Using their approach, we derive here a general expression for estimating the resolution of the ith exit of the MMO-DMA for given operating conditions.…”
Section: Resolution Of the Mmo-dmamentioning
confidence: 97%
“…Particles, the electrical migration of which is balanced by the cross-flow, are advected between the porous electrodes by a smaller sample flow. The performance of the OMAC is similar to that of the DMA, except that the voltage at which diffusion begins to degrade resolution is much lower, and scales as V / R nd (Downard et al 2011) rather than as V / R 2 nd as in the DMA (Stolzenburg 1988;Flagan 1999). Because the length scale over which diffusion must act to affect resolution is the entire channel width, b, in the OMAC, but only » bb in the DMA, the dynamic range of the OMAC can, in theory, be made much larger than that of any DMA of comparable resolving power and dimensions.…”
Section: Advancing Nanometer Particle Classificationmentioning
confidence: 75%
“…with r 2 D 0.96, shown in Figure 8h. An asymptotic analysis of the transfer function for an idealized, rectilinear OMAC (Downard et al 2011) supports the observed dependence of h trans on b. The experimental h trans values are compared with those predicted by Equation (25) in Figure 8i.…”
Section: Diffusional Broadening Parametermentioning
confidence: 81%
See 1 more Smart Citation